Proceedings of the 4th International Conference on the Durability of Concrete Structures 2014
DOI: 10.5703/1288284315417
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Uniaxial Electrical Measurements on Layered Cementitious Composites having Cylindrical and Prismatic Geometries

Abstract: Electrical measurements are becoming a common method to assess the transport properties of concrete. For a saturated homogenous system, the surface resistance and the uniaxial resistance measurements provide equivalent measures of resistivity once geometry is appropriately taken into account. However, cementitious systems are not always homogenous. This article compares bulk and surface resistance measurements in cementitious materials intentionally composed of layered materials (i.e., layers with different re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…In this approach, if there is heterogeneity, the values from the two tests will be different. This difference can give an indication as to whether the surface layer is more or less resistive [21]. Similarly, correlation between surface and bulk resistivity found in other studies indicated a strong relationship between the resistivity values when the appropriate geometry factor was applied [8,37]:…”
Section: Correlation Between Surface and Bulk Electrical Resistivitymentioning
confidence: 94%
See 3 more Smart Citations
“…In this approach, if there is heterogeneity, the values from the two tests will be different. This difference can give an indication as to whether the surface layer is more or less resistive [21]. Similarly, correlation between surface and bulk resistivity found in other studies indicated a strong relationship between the resistivity values when the appropriate geometry factor was applied [8,37]:…”
Section: Correlation Between Surface and Bulk Electrical Resistivitymentioning
confidence: 94%
“…Based on the reported data, it can be concluded that a strong relationship exists between resistivity measured by surface and bulk tests. However, in practical cases, caution is needed for multilayered cementitious composite systems as electrical current flows differently in these two techniques and for the types of layered electrical properties that can occur due to moisture gradients, chemical changes, and ionic gradients [21]. More complicated situations for resistivity measurement that arise during field measurements where seasonal and wet/drying might take place at the tidal section on partially …”
Section: Correlation Between Surface and Bulk Electrical Resistivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Surface and uniaxial measurements of the resistance of hardened concrete cylinders are performed at various ages, while twin steel (screw rod) probes are embedded in a cylinder of each fresh concrete mixture to monitor its ''bulk'' resistance during the first day of curing [3]. The goal of the electrical measurements on the hardened concretes is to provide an indication of their expected durability, capitalizing on the relationship between conductivity and diffusivity [4][5][6] and the observations that reinforced concretes with higher resistivity generally exhibit lower corrosion rates [7]. For the fresh concrete, the goal is to use the initial measurements of electrical resistance to anticipate the subsequent setting time of each concrete mixture [3,8].…”
Section: Introductionmentioning
confidence: 99%